1993
DOI: 10.1007/bf00316473
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics of the ?2-adrenoceptor agonist, tulobuterol, given transdermally and by inhalation

Abstract: We have studied the pharmacokinetics of tulobuterol given transdermally or by aerosol inhalation in healthy male volunteers. Tulobuterol was rapidly absorbed after inhalation, with a tmax of 0.8-1.5 h. The Cmax and the AUC increased linearly with dose. Tulobuterol was well absorbed after transdermal administration, with an absorption lag-time of about 4 h. The Cmax and AUC increased linearly with dose and the tmax was about 9-12 h. The mean percentage of drug absorbed during the application of a patch for 24 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 11 publications
0
32
0
Order By: Relevance
“…9 When the 2 mg tulobuterol patch was administered to healthy adults, it was found to be well absorbed, with an absorption lag-time of about four hours. Serum tulobuterol concentrations peaked at 9-12 hours and decreased gradually over the 24 hours following application of the patch.…”
Section: Pharmacokineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 When the 2 mg tulobuterol patch was administered to healthy adults, it was found to be well absorbed, with an absorption lag-time of about four hours. Serum tulobuterol concentrations peaked at 9-12 hours and decreased gradually over the 24 hours following application of the patch.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…A pharmacokinetic study 9 reported that tulobuterol released from the patch did not accumulate during repeated transdermal application in healthy adults. It was well tolerated, except for an increase in heart rate of 10-20 beats per minute after five consecutive applications of a 4 mg patch.…”
Section: Safetymentioning
confidence: 99%
“…The weighted mean of the serum concentration obtained from nine clinical trials of the tulobuterol TTS (Hokunalin ® tape) which have been shown in the prescribing information respectively was used as the comparative. 13,[26][27][28][29][30][31][32][33] Those clinical trials were carried out in 5 to 48 healthy Japanese male volunteers.…”
Section: Calculation Of Clinical Pharmacokinetic Parameters Using Thementioning
confidence: 99%
“…11,12) However, as for several commercially-available TTSs, the blood drug concentration reaches the peak value once and then falls during application. 13,14) The fall of blood concentration is caused by decline of the skin-surface concentration of the drug, that is, depletion of the drug. In this instance, the predicted blood concentration profile obtained from the abovementioned simplified model is quite different from the experimental data because the decline of the blood concentration is not considered.…”
mentioning
confidence: 99%
“…46) Many reports demonstrate the rationale behind chronotherapy. [47][48][49] However, much of the drug delivery research over the past decades has focused on a constant drug release rate. The reason why the majority of DDS is designed with little emphasis on proven oscillatory phenomena may be found in drug delivery limitations.…”
Section: Influence Of Biological Rhythms On Phar-macodynamics and Phamentioning
confidence: 99%